AN ANALYSIS OF THE EFFECT OF EDUCATION LEVEL, AGE, AND WASTE PRICE ON THE PARTICIPATION OF WASTE BANK MEMBERS IN KESIMAN KERTALANGU VILLAGE - I GUSTI AYU EKA CHRYSTINAYUNI; Ni Made Tisnawati (CV. Adiba Aisha Amira, 2025)
This study analyzes the influence of education level, age, and waste prices on the participation of waste bank members in Kesiman Kertalangu Village. The main focus of this research is to address the increasing volume of waste in Denpasar and the low level of participation in local waste bank initiatives. This research employs an associative quantitative approach, with education level, age, and waste prices as the independent variables, and community participation as the dependent variable. Data were collected from 73 respondents, who are part of the 268 registered customers of the waste bank in Kesiman Kertalangu Village, determined using an accidental sampling method. The results of the study conclude that education level, age, and waste prices simultaneously have a significant influence on community participation in the waste bank program in Kesiman Kertalangu Village. Partially, the variables of education level, age, and waste prices also show a positive and significant influence on community participation. Higher education levels increase awareness and understanding; older age groups tend to participate more actively; and higher waste prices serve as an economic incentive.